2002
DOI: 10.1111/j.1746-1561.2002.tb07338.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Physical Activity Between Black and White Girls Living in Rural and Urban Areas

Abstract: This study examined the relationship of race and rural/urban setting to physical, behavioral, psychosocial, and environmental factors associated with physical activity. Subjects included 1,668 eighth-grade girls from 31 middle schools: 933 from urban settings, and 735 from rural settings. Forty-six percent of urban girls and 59% of rural girls were Black. One-way and two-way ANOVAs with school as a covariate were used to analyze the data. Results indicated that most differences were associated with race rather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
107
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(120 citation statements)
references
References 15 publications
11
107
2
Order By: Relevance
“…9 Other research has identified adolescence as a time when females, particularly African Americans, demonstrate reduced and minimal physical activity participation. 7 Substantial differences in self-reported physical activity between Caucasian and African American adolescent females have been found in previous research studies. 7,9 One study revealed that by the age of 17, 56% of African American and 31% of Caucasian female participants reported no leisure time physical activity in the previous 7 days.…”
Section: Ethnic Differencesmentioning
confidence: 93%
See 3 more Smart Citations
“…9 Other research has identified adolescence as a time when females, particularly African Americans, demonstrate reduced and minimal physical activity participation. 7 Substantial differences in self-reported physical activity between Caucasian and African American adolescent females have been found in previous research studies. 7,9 One study revealed that by the age of 17, 56% of African American and 31% of Caucasian female participants reported no leisure time physical activity in the previous 7 days.…”
Section: Ethnic Differencesmentioning
confidence: 93%
“…7 Substantial differences in self-reported physical activity between Caucasian and African American adolescent females have been found in previous research studies. 7,9 One study revealed that by the age of 17, 56% of African American and 31% of Caucasian female participants reported no leisure time physical activity in the previous 7 days. 7 Despite such relatively high percentages of inactivity in both groups, African American girls appear to need the greatest amount of support to adopt physically active lifestyles.…”
Section: Ethnic Differencesmentioning
confidence: 93%
See 2 more Smart Citations
“…This suggests that childhood setting affected the respondents' activities and experiences. Similarly, rural children reported having more active involvement in nature-related activities than urban children in South Carolina, United States [48,49], and the United Kingdom [50,51]. The significant interaction of age and childhood settings indicates that young and middle-aged people with urban childhood had more decline in nature-related activities than rural people as presented in result section (Figure 3).…”
Section: Differences In Nature-related Experiences In Childhood Amongmentioning
confidence: 77%